2006
DOI: 10.1007/s11248-006-9008-4
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Mercury-Hyperaccumulating Plants through Transgenic Expression of the Bacterial Mercury Membrane Transport Protein MerC

Abstract: The merC gene from Acidithiobacillus ferrooxidans functions as a mercury uptake pump. MerC protein localizes in the cytoplasmic membrane of plant cells. When Arabidopsis thaliana and tobacco plants were transformed with the merC gene under the control of the Cauliflower mosaic virus 35S promoter, the resulting overexpression of merC rendered the host plants hypersensitive to Hg2+ and they accumulated approximately twice as much Hg2+ ion as the wild type plants. Thus, bacterial mercuric ion transporters such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 38 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…The observations reported in this communication suggest that plasmid transfer and controlled gene expression can render many bacteria (Schaefer et al, 2004) and plants (Sasaki et al, 2006) useful for bioremedial Hg 2+ detoxification. When mercury toxicity is problematic, as it is in many mining environments and their surroundings, transfer of a mercuric resistance plasmid to a naturally occurring, dominant, microbial population could render that bacterial population effective as an agent of bioremediation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The observations reported in this communication suggest that plasmid transfer and controlled gene expression can render many bacteria (Schaefer et al, 2004) and plants (Sasaki et al, 2006) useful for bioremedial Hg 2+ detoxification. When mercury toxicity is problematic, as it is in many mining environments and their surroundings, transfer of a mercuric resistance plasmid to a naturally occurring, dominant, microbial population could render that bacterial population effective as an agent of bioremediation.…”
Section: Discussionmentioning
confidence: 74%
“…Equivalent plasmids have been isolated from several bacteria indicating frequent lateral transfer. Sasaki et al (2006) have recently transferred the merC gene of Acdithiobacillus ferrooxidans into Arabidopsis thaliana and tobacco plants, and demonstrated that the plants accumulate increased amounts of Hg 2+ . The potential of such transgenic plants for phytoremediation is noteworthy.…”
mentioning
confidence: 99%
“…Arazi et al [ 29 ] reported that the overexpression of a plasma membrane protein (NtCBP4) in transgenic tobacco plants increased Pb accumulation, but also significantly enhanced the plant’s sensitivity to the metal. By the same token, the expression of the MerC gene in Arabidopsis and tobacco increased Hg accumulation 2-fold in relation to wild type plants, but rendered the transgenic plants hypersensitive to Hg [ 30 ].…”
Section: Genetically Engineered Phytoremediationmentioning
confidence: 99%
“…Twice as much mercury was extracted by Arabidopsis thaliana and tobacco plants when they were modified with the merC gene (Sasaki et al 2006). At the end of extraction/accumulation, the plants will have to be disposed of appropriately by drying, incinerating, gasifying, pyrolysis, acid extraction, anaerobic digestion, or extracting the oil and chlorophyll fibers (Mulligan et al 2001a).…”
Section: Other Promising Technologiesmentioning
confidence: 99%